(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Irwandhi, Kamaluddin NN, Khumairah FH, Prihatiningsih N, Simarmata T. 2025. Assessment of local wisdom biofertilizer formulas on enhancing microbial diversity and photosynthate allocation in acid-stressed maize. Asian J Agric 9: 112-121. The use of biofertilizers derived from local wisdom practices presents a promising sustainable agricultural strategy for enhancing crop resilience in acidic soils. This study aimed to assess the effectiveness of the Local Wisdom Biofertilizer (LWB) formula by examining the chemical and biological characteristics of various LWB formulations and their impact on growth-promoting microorganisms (GPMs) diversity (bacteria, fungi, and actinomycetes) and maize growth characters. A Randomized Complete Block Design (RCBD) was employed, testing six LWB formulations (F1 to F6) at four dosage levels (0, 2, 4, and 6%) to assess their effects on key growth traits of maize grown in suboptimal soils. Results revealed significant variation in organic carbon, nitrogen, phosphorus, and potassium across formulations, with F3 demonstrating the highest organic carbon (14.80%) and potassium (0.08%). In comparison, F2 exhibited the highest total nitrogen (4.07%), and F5 had the highest phosphorus content (0.03%). Formulation F6 demonstrated the highest concentrations of nitrogen-fixing bacteria (NFB) and phosphate-solubilizing bacteria (PSB) among the treatments. The treatments F3K3, F4K3, F5K1, F5K3, F6K1, and F6K2 effectively enhanced maize plant height, with F3K3 and F5K3 having a particularly significant effect on chlorophyll content. Additionally, F1K1 led to the largest bacterial population, F5K1 supported the greatest fungal population, and F6K2 exhibited the highest actinomycetes population. Correlation analysis indicated a negligible relationship between chlorophyll content and other agronomic traits, with values ranging from -0.02 to 0.01. Principal Component Analysis further analyzed the influence of LWB on various plant traits. These findings underscore the potential of integrating local wisdom biofertilizers into sustainable soil management practices, especially in regions grappling with soil acidity. Future research should delve into the microbial and biochemical mechanisms underlying these benefits to optimize biofertilizer formulations for broader agroecological applications.